2020
DOI: 10.21203/rs.3.rs-15568/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional status and dietary diversity of school-age children living with HIV: a cross sectional study in Phnom Penh, Cambodia

Abstract: Background: HIV/AIDS continues to be a major public health concern for children. Each day, worldwide, approximately 440 children became newly infected with HIV, and 270 children died from AIDS-related causes in 2018. Poor nutrition has been associated with accelerated disease progression, and sufficient dietary diversity is considered a key to improve children’s nutritional status. Therefore, this study aims to 1) examine nutritional status of school-age children living with HIV in Phnom Penh, Cambodia, and 2)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…For patients who took up fruits and vegetables following NC, recovery was higher at 94.8% compared to 2.7% who took proteins only for 12 weeks. Yasuoka et al (2020) revealed that dietary diversity may not necessarily promote nutritional recovery following NC but a combination of other factors. According to Kissa et al (2014), a study in Tanzania showed recovery from MAM was from 1.7% -2.4% following food demonstration, which implied maximisation of NC as an intervention to better prognosis from MAM.…”
Section: Dietary Diversitymentioning
confidence: 99%
“…For patients who took up fruits and vegetables following NC, recovery was higher at 94.8% compared to 2.7% who took proteins only for 12 weeks. Yasuoka et al (2020) revealed that dietary diversity may not necessarily promote nutritional recovery following NC but a combination of other factors. According to Kissa et al (2014), a study in Tanzania showed recovery from MAM was from 1.7% -2.4% following food demonstration, which implied maximisation of NC as an intervention to better prognosis from MAM.…”
Section: Dietary Diversitymentioning
confidence: 99%